Analisis Implementasi Program Matrikulasi Bahasa Arab Di SD El Haqqa Quranic School Pekanbaru: Pendekatan Inovatif Sebagai Langkah Awal Pembelajaran di Tahun Ajaran Baru - Syahri, Hanifa; Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Arabic Matriculation Program at SD El Haqqa Quranic School Pekanbaru from the perspective of curriculum development as an innovative approach at the beginning of the academic year. The program is implemented for all students from grades I to VI to strengthen their basic Arabic competencies and promote the habitual use of Arabic within the school environment. This research employs a case study method, as the program is not widely applied in other elementary schools. Data were collected through observation, interviews, and documentation during the program’s implementation. The findings reveal that the matriculation program significantly contributes to improving students’ Arabic speaking skills, while also enhancing their learning motivation and self-confidence. Therefore, the implementation of the Arabic Matriculation Program can serve as an innovative model in developing Arabic language curricula in Islamic elementary education.